A two-step hydrothermal synthesis of TiO2/C/FeS2 composite as high performance anode for lithium ion batteries. (1st August 2021) - Li, Guanghui; Cao, Shiyue; Fu, Likang; Wan, Shuyun; Liu, Qiming
Highlights: TiO2 /C/FeS2 composite was successfully prepared via a novel strategy of two-step hydrothermal method. TiO2 nanoparticles were distributed on the surfaces of FeS2 and carbon rods. The specific surface area of TiO2 /C/FeS2 was as high as 126.8 m 2 g −1 . TiO2 /C/FeS2 exhibited high specific capacity of 1057.5 mAh g −1 at 0.2 A g −1 and excellent long-term cycling performance (541.4 mAh g −1 at 4 A g −1 after 1600 cycles). Abstract: TiO2 /C/FeS2 composite as high performance anode material for lithium ion batteries (LIBs) is prepared via a two-step hydrothermal strategy. The high specific surface area of TiO2 /C/FeS2 enlarge the contact area between electrode and electrolyte. Moreover, external TiO2 nanoparticles and carbon rods effectively mitigate the volume expansion of FeS2 . TiO2 /C/FeS2 composite exhibits a high specific capacity of 1057.5 mAh g −1 at 0.2 A g −1, and superior long-term cycling performance. Additionally, TiO2 /C/FeS2 electrode shows pseudocapacitive behavior during cycles, which is contributed to lithium storage. This work reveals the potential application of TiO2 /C/FeS2 composite as high performance anode material.